Improving Mathematics Learning Outcomes on Area Material with Non-Standard Units through Concrete Object Media at MI Ma'arif NU Karangjoho Pengadegan Purbalingga - Aprianto, Widi (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to determine the increase in student activity and learning outcomes by using concrete object media in Mathematics learning on the material of non-standard unit area for class III MI Ma'arif Nu Karangjoho. This type of research is classroom action research with the research subjects of class III MI Ma'arif NU Karangjoho students totaling 14 students, consisting of 6 male students and 8 female students. This research was conducted by class III teachers who acted as researchers. The data collection methods used were Post-test and observation. The instruments used were teacher and student activity observation sheets used to observe students and teachers in implementing Mathematics learning using concrete object media. The research data were analyzed descriptively qualitatively and quantitatively. The results of this study indicate that the application of concrete object media in Mathematics lessons can increase the activity and learning outcomes of class III MI Ma'arif NU Karangjoho students. The results showed an increase in learning from pre-action, namely 21.43% in the low category to 85.71% in cycle I, included in the high category and increased in cycle II to 100% in the very high category and has reached the word perfect. In addition, the achievement of 100% of students completing the program can be said to be in a very high category and has met the established success criteria, namely 80%.